Contaminants in the Urban Environment: Dioxins - Yun-Ya Yang; Gurpal S. Toor (EDIS)
Dioxins are among the most toxic chemicals on the earth. They are by-products of a number of human activities such as combustion of fuels and wastes containing polyvinyl chloride (PVC), chlorine bleaching of paper products, and selected industrial processes. Current releases of dioxins by humans are due to the combustion of fuels and burning of household trash. The good news is that levels of dioxins in the environment have decreased in the United States throughout the past 30 years due to the improved emission controls and regulatory activities. But dioxins break down slowly, so they remain in the environment for a long time and accumulate in the food chain. Long-term exposure to dioxins can harm immune system, nervous system, endocrine system, and reproductive functions. This 7-page fact sheet discusses the sources, emission trends, and impacts of dioxins as well as the ways to minimize exposure to dioxins. Written by Yun-Ya Yang and Gurpal S. Toor, and published by the UF Department of Soil and Water Science, July 2015.